2004
DOI: 10.1186/bcr899
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptomic changes in human breast cancer progression as determined by serial analysis of gene expression

Abstract: Introduction Genomic and transcriptomic alterations affecting key cellular processes such us cell proliferation, differentiation and genomic stability are considered crucial for the development and progression of cancer. Most invasive breast carcinomas are known to derive from precursor in situ lesions. It is proposed that major global expression abnormalities occur in the transition from normal to premalignant stages and further progression to invasive stages. Serial analysis of gene expression (SAGE) was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 46 publications
7
106
2
Order By: Relevance
“…Loss of heterozygosity in this region was observed in several solid tumors, including breast cancer, ovarian cancer, lung cancer and BeckwithWiedemann syndrome (Negrini et al, 1995;Tran and Newsham, 1996;Catchpoole et al, 1997;Lu et al, 1997;O'Briant and Bepler, 1997;Karnik et al, 1998). We detected downregulated IFITM1 expression in 20 out of 28 clinical hepatoma samples, consistent with the reported transcriptional downregulation of IFITM1 in low-grade diffuse astrocytomas and breast cancer (Huang et al, 2000;Abba et al, 2004). Recently, it was suggested that high IFITM1 expression correlated with improved survival in chronic myeloid leukemia patients (Akyerli et al, 2005).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Loss of heterozygosity in this region was observed in several solid tumors, including breast cancer, ovarian cancer, lung cancer and BeckwithWiedemann syndrome (Negrini et al, 1995;Tran and Newsham, 1996;Catchpoole et al, 1997;Lu et al, 1997;O'Briant and Bepler, 1997;Karnik et al, 1998). We detected downregulated IFITM1 expression in 20 out of 28 clinical hepatoma samples, consistent with the reported transcriptional downregulation of IFITM1 in low-grade diffuse astrocytomas and breast cancer (Huang et al, 2000;Abba et al, 2004). Recently, it was suggested that high IFITM1 expression correlated with improved survival in chronic myeloid leukemia patients (Akyerli et al, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, it has been reported that transcriptional expression of IFITM1 is downregulated in low-grade diffuse astrocytomas and breast cancer (Huang et al, 2000;Abba et al, 2004). In this study, we report that IFITM1 mediates the antiproliferative effect of IFN-g and arrests cell proliferation in a p53-dependent manner.…”
Section: Introductionsupporting
confidence: 58%
“…12,13,32,37 However, 42% of the ERa-negative tumors showed high, and 17% of the ERa-positive tumors showed low FOXA1 expression; and FOXA1 levels were inversely correlated with lympho-vascular invasion, even after adjustment for ERa status. These data suggest that at least some of FOXA1 activities in breast cancer are ERa-independent.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen III disrupts formation of dense, organized collagen I networks, resulting in softer ECM [94]. Loss of collagen III in mouse models is associated with tumor aggressiveness [94], though Col III is often observed to be overexpressed with increasing tumor grade [20,81,82,95]. Furthermore, reductions in collagen I density via TGFβ blockade likewise suggest that altering collagen network structure is a potential therapeutic target [96].…”
Section: Microstructure Biomechanics and Crosslinkingmentioning
confidence: 99%